PENGARUH SUBSTITUSI LIMBAH BAN BEKAS DALAM CAMPURAN AC-WC TERHADAP KARAKTERISTIK CAMPURAN - Yattaqi, Hariz Athhar; Riyanto, Sugeng; Pudjowati, Utami Retno (Prokons: Jurnal Teknik Sipil, 2024)
Waste is the byproduct of a company or activity that includes dangerous or poisonous substances which, owing to their inherent properties, concentration, and quantity, may directly or indirectly jeopardize the environment, human health, and the existence of other organisms. Tire trash is categorized as a kind of garbage that is not readily biodegradable, requiring more innovation and effort to get beneficial outcomes. Laston AC-WC is a composite material used for road surfacing that directly interacts with vehicle wheels. Asphalt will be replaced as one of the components of asphalt concrete. Asphalt serves as both an aggregate binder and a black adhesive. The purpose of the study was to analyze how much tire waste affects the concrete asphalt mixture with variations in asphalt waste content (6%, 8%, 10%, 12%, 14%). This research was carried out in the Road Material Test laboratory of the Civil Engineering Building of the Malang State Polytechnic. The method used involved a total of 36 test pieces, of which 21 were for KAO and 15 were for waste tires. The results of testing the laston AC-WC mixture with the non-substitution marshall method obtained a KAO of 6.75%. The variation of tire waste was 6% with a stability value of 1382.08 Kg, Flow 2.28 Kg, VFA 74.36%, VIM 4.08, VMA 15.59 and MQ 483.98 Kg/mm. Meanwhile, the variation of 8% tire waste gets a stability value of 1230.08Kg, Flow 2.25mm, VFA 82.10%, VIM 3.34%, VMA 18.61%, and MQ 453.94Kg/mm. The estimated cost owned by Laston AC-WC with 8% tire waste substitution at a price of Rp.1,651,936.24/ton.